Prospects of legal regulation in the field of electronic waste management in the context of a circular economy - Ilyassova, G.; Nukusheva, A.; Arenova, L.; Karzhassova, G.; Akimzhanova, M. (My University, 2021)
The purpose of the study is to identify the existing problems in the field of electronic waste management and to consider the possibilities and prospects of their legislative regulation. The method of political and legal analysis and the legal forecasting method made it possible to trace the evolution of international legislation in the field of management and disposal of electronic waste, the dynamics of its development, and make a forecast regarding possible vectors of its development. The research aims to answer the question of what are the existing problems in the field of e-waste management within their interdependence with the “circular economy” concept and what are the possibilities and prospects for their legislative regulation. The study analyzes the perspective directions of the formation of international policy and legal regulation in the field of electronic equipment waste management and disposal. The issues of the transfer of electronic waste to developing countries, the difficulties associated with the lack of proper legal regulation and enforcement in these countries, the protection of the labor rights of workers in the field of electronic waste disposal were considered. In addition, the practice of application and prospects for introducing into the legislation the principle of extended producer responsibility are considered. This study is intended to contribute to a better understanding of current trends in the field of electronic waste management in order to demonstrate the need to improve the existing international legal framework, adapt it to modern challenges and show the main directions of its changes.
Keywords: Basel Convention; Electronic equipment; Legislation; Linear economy; Processing; Recycling